2001
DOI: 10.1046/j.1365-2265.2001.1139/cn2155.x
|View full text |Cite
|
Sign up to set email alerts
|

T lymphopaenia in relation to body mass index and TNF-alpha in human obesity: adequate weight reduction can be corrective

Abstract: Our results suggest that subsets of T cell populations and their function may be reduced in human obesity, and that this may be related, at least in part, to the elevated TNF-alpha production. Furthermore, this T cell dysfunction can be recovered by adequate weight reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
1
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 33 publications
8
96
1
12
Order By: Relevance
“…Thus, both radiation exposure and the obesity-related metabolic profile, potentially related to enhanced inflammation, are considered as accelerators of human T-cell immunological aging. On the other hand, this study observed higher percentages of total T, T H 1, CD8 T and B cells along with obesityrelated metabolic indicators, especially with low HDL cholesterol; these results are generally in accord with those from other human studies (10)(11)(12)(32)(33)(34)(35)(36)(37). In animal models, a direct link between low HDL cholesterol levels and the vast expansion of various types of immune cells (T and B cells, macrophages and dendritic cells) has been established (38): A postulated mechanism is that HDL reduces cholesterol content in membrane lipid rafts, which can suppress intracellular signaling in such immune cells (38).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, both radiation exposure and the obesity-related metabolic profile, potentially related to enhanced inflammation, are considered as accelerators of human T-cell immunological aging. On the other hand, this study observed higher percentages of total T, T H 1, CD8 T and B cells along with obesityrelated metabolic indicators, especially with low HDL cholesterol; these results are generally in accord with those from other human studies (10)(11)(12)(32)(33)(34)(35)(36)(37). In animal models, a direct link between low HDL cholesterol levels and the vast expansion of various types of immune cells (T and B cells, macrophages and dendritic cells) has been established (38): A postulated mechanism is that HDL reduces cholesterol content in membrane lipid rafts, which can suppress intracellular signaling in such immune cells (38).…”
Section: Discussionsupporting
confidence: 92%
“…Decreased inflammation after weight loss has been associated with improvement in insulin sensitivity and iron status, among other conditions (47,(73)(74)(75). Most weight loss studies have also shown an improvement in cell-mediated immune response measured as lymphocyte proliferation (65,71,76,77). For example, Ahmed et al (76) showed an improvement in lymphoproliferation after a 10 or 30% CR over 6 mo.…”
Section: Weight Loss In Obese Individuals and Immune Functionmentioning
confidence: 99%
“…Moreover, individuals with a higher body mass index are reported to be at an increased risk of infection and infection-related mortality (as reviewed by Falagas and Kompoti 2 ), have poor antibody responses to vaccines [3][4][5] and have immune cells with a reduced capacity to proliferate when stimulated with T-cell mitogens. 6,7 More recently, a higher prevalence of atopic diseases has been reported in the overweight population, suggesting heightened activation of T-helper 2 (Th2) cells (as reviewed by Hersoug and Linneberg 8 ). Adipose tissue has been shown to be actively involved in producing and secreting inflammatory mediators, including leptin, adiponectin, monocyte chemoattractant protein-1, IL-6 and tumor necrosis factor-a.…”
Section: Introductionmentioning
confidence: 99%